Analyzing the Roles of Aesthetic Characteristics and Product Quality in Shaping Product Cost and Purchasing Decisions for Wooden Gravestones in Samarinda : Evidence from a Mixed Methods Study. - Rony H; Darius Shyafary, Ditha Nizaora, Leny Marlina (Jurnal Mirai Management, 2025)
This study examines the influence of aesthetics and product quality on Cost of Production (HPP) and purchasing decisions for wooden gravestones in Samarinda. The research employs an explanatory sequential mixed-methods approach: (1) a quantitative phase involving a survey of 120 consumers who have purchased or considered purchasing wooden gravestones; and (2) a qualitative phase consisting of in-depth interviews with 10 craftsmen/sellers and 8 selected consumers. The main variables include aesthetics (X1), product quality (X2), HPP (M), and purchasing decisions (Y). Quantitative analysis was conducted using descriptive statistics, reliability testing, factor analysis, multiple regression, and mediation testing (Sobel/bootstrapping). The findings reveal that aesthetics—particularly the aesthetic value of carving motifs—and product quality have a positive and significant effect on purchasing decisions. Both variables also influence HPP, and HPP partially mediates the relationship between aesthetics/product quality and purchasing decisions. Qualitative insights support the quantitative results: consumers generally make purchasing decisions based on the perceived aesthetic value and carved design motifs of ulin wood gravestones. The selection of aesthetically appealing motifs contributes to higher production costs and product value. These findings have important implications for craftsmen, particularly MSMEs, in developing aesthetic design strategies, determining price structures, and selecting materials and production costs in an accountable manner. Keywords: Aesthetics, product quality, cost of production, purchasing decisions, wooden gravestones, MSMEs, mixed-methods